Portrait of Jules François Joubert (1877)
Printed portrait of French scientist and professor Jules Francois Joubert (1834-1910), who assisted French chemist, biologist and microbiologist Louis Pasteur (1822-1895). Joubert collaborated with Pasteur in 1877, observing how cultures of the anthrax bacilli become inhibited when contaminated with molds. Some references attribute Pasteur with identifying the Penicillium notatum strain leading to the development of penicillin. Joubert is also known for his work measuring electromagnetic waves.
Keywords: Penicillin; Bacillus anthracis; Chemists; Pasteur, Louis, 1822-1895; Joubert, Jules François, 1834-1910; Penicillium notatum; Electromagnetic waves; Portraits; Scientists; College teachers